Application of Path Analysis in Aceh Poverty Modeling - Mulia, Rika; Dian Safitri, Winny (Transcendent Journal of Mathematics and Applications, 2022)
The Human Development Index (HDI) is an important indicator of the success of efforts to improve the quality of human life. As a measure of quality of life, HDI is based on three basic aspects including aspects of health, education and a decent standard of living. There are several factors that can affect poverty, such as Zakat, Infaq and Sadaqah (ZIS), and the Family Hope Program (PKH). This study aims to determine the effect of the amount of ZIS funds and the number of recipients of PKH on poverty and HDI in Aceh in 2015-2020. This study uses a quantitative approach. The data analysis method in this study uses path analysis and Sobel test. The results showed that the amount of ZIS funds had a negative and insignificant effect on poverty in Aceh. The number of PKH recipients has a positive and insignificant effect on poverty in Aceh. The amount of ZIS funds has a positive and significant effect on HDI. The number of PKH recipients has a negative and insignificant effect on HDI in Aceh. Poverty has a negative and significant effect on HDI in Aceh. Poverty is able to mediate the effect of the amount of ZIS funds on HDI in Aceh. Poverty is unable to mediate the effect of the number of PKH recipients on the HDI in Aceh.